Metamodels for Optimum Design of Outer-Rotor Synchronous Reluctance Motor - Lavrinovicha Ludmila; Dobriyan Roman; Onzevs Oskars (Electrical, Control and Communication Engineering)
A new design of synchronous reluctance motor with segment-shaped outer rotor is presented and investigated in this paper. In order to obtain correct recommendations for optimal design of the studied synchronous reluctance motor, analytical relations of motor electromagnetic parameters and geometrical dimensions (also known as metamodels) have been synthesized. Electromagnetic parameters, which have been used for metamodels synthesis, are obtained by means of magnetostatic field numerical calculations with finite element method using software QuickField.